Edukasi Penerapan Healing Environment sebagai Upaya Pengendalian Stres pada Stroke Survivors dalam Mencegah Serangan Berulang - Dewi, Ni Luh Putu Thrisna; Wati, Ni Made Nopita; Lisnawati, Ketut; Sri Sanjiwani, Anak Agung; Sudarma, I Nyoman (Jurnal Abdimas Kesehatan (JAK), 2024)
Stroke is the second leading cause of death in the world and the third leading cause of disability, with incidence and prevalence increasing significantly. In Indonesia, the prevalence of stroke is high, mainly due to the lack of control of risk factors and slow adaptation to a healthy lifestyle after the attack. Stress is identified as one of the main factors that aggravate the physical condition and hinder the recovery process in stroke survivors. This community service aims to provide education about the healing environment method as an effort to control stress to prevent recurrent attacks in stroke survivors in Bangli Regency, Bali. This activity was carried out from December 2023 to January 2024, with a community service method in the form of education and demonstration for three days on how to create a healing environment that includes aspects of safety, physical and psychological comfort, social support, access to nature, art, music, and privacy which was attended by 20 stroke survivors. Results showed that the majority of participants had high blood pressure (80%) and normal blood glucose (85%). The increase in participants' knowledge about the healing environment was reflected in the pre-test results which showed 75% of participants had low knowledge, while the post-test showed an increase in sufficient knowledge in 80% of participants. This education helped participants recognize the factors that cause stress and manage stress effectively. The conclusion of this activity shows that the healing environment method can help reduce stress, accelerate recovery, and prevent recurrent stroke attacks. Thus, this method can improve the overall quality of life of stroke patients. The program emphasized the importance of a holistic approach that includes physical, psychological, social, and spiritual aspects to optimize the recovery of stroke patients and prevent further complications.